The Role of Talent Management in Public Organizations - Wahyuni, Luh Ria; Suwena, Kadek Rai (Amkop Management Accounting Review (AMAR), 2025)
The quality of management in the public sector is an important issue that is considered globally. The success of the performance of public sector organizations is measured by their effectiveness and efficiency in providing services to the community, so that the performance of public sector organizations is in the spotlight of all levels of society. The government's image in the community is suffering due to the poor quality of public services provided by its officials. Optimal human resource management is an important factor in advancing organizations today. Without adequate human resource planning, organizational growth becomes difficult to achieve. This study examines how talent management supports the optimization of public sector organizational performance. The research method used is a systematic literature review, by classifying, reviewing or analyzing information obtained through reference sources such as journals, books, and important data related to organizational performance and talent management, which are then selected systematically. From the literature review process, it can be concluded that the implementation of effective talent management in the public sector is very necessary to create long-term organizational performance success and as a strategy to prepare competent civil servant in facing the complexity of bureaucracy in the future. By understanding and implementing talent management effectively, organizations can create sustainable competitive advantages while encouraging growth and innovation in various operational lines.